INVESTIGATE OF VIRULENCE- GENES OF PASTEURELLA MULTOCIDA TYPES AND ANTIBIOTIC SUSCEPTIBILITY IN BUFFALOES IN MARSHES OF SOUTH OF IRAQ - Jalil Abed Gatie (University of Thi-Qar Journal of agricultural research, 2020)
This study was conducted to investigate the incidence of Pasteurella multocida in buffaloes in south of Iraq. A total 393 of different ages and sexes, were clinically examined. Nasal swabs and blood samples were taken . Enrich and Selective medias ,biochemical tests and Gram stain were used. also used antibiotic susceptibility. All positive cases confirmed by polymerase chain reaction with specific primer to P. multocida then use specific primers to detect P.multocida A,B. Also use specific primers to detect some virulence gene (pfhA ; nanH ; ompA ; hgbA) .Prevalence of P. multocida types in marshes area which it appear 35 samples 35% to type A and it significant variation at (P≤0.05) than types (B) which found 65 samples 65 % also it significant variation. Capsular typing of 100 isolates in marshes appeared 35 (35%) to type A , 65 (65 %) to type B with significantly variation between types . Distribution of virulence- genes appeared 75 (75%) to ompA , hgbA 59 (59 %) , nanH 46 ( 46 %) and pfhA 33(33%) with significantly variation between genes .No significant variation of prevalence of virulence- genes between infected and non-infected. Also prevalence of Pasteurella multocida virulence- genes which it appear 49(74.2%);26(76.4%)to ompA , 41(62.1), 18(52.9) to hgbA ; 27(40.9), 19(55.9) to nanH and 20(30,3) ,13(38.3) to pfhA for diseased and non diseased respectively .Prevalence of P.multocida virulence- genes appeared 25(71.4); 50(76.9); to ompA , 18(51.4), 41(63.1); to hgbA ; 16(45), 30(47.6) to nanh and 16(45.7) , 17(27.0); to pfhA for type A and type B respectively.The antibiotics susceptibility of 52 isolated which from 25 type B , 25 type A and showed that : Cefotaxime , Cefitrixone, Azithromycin and Tilmicosin founded 100% susceptibility ,followed by Chloromphinocol as 96-92%, Tetracycline 40-32% while Ampicilline32-28 %.Conclusions of present study are : P. multocida endemic in buffaloes in south of Iraq. Recoded of virulence genes of P. multocida in buffaloes in Iraq. Cefotaxime , Cefitrixone, Azithromycin and Tilmicosin are the best choice to treatment. PCR assay is best technique to diagnosis and detect.